The Overview of Village Community of the 3M (Washing Hands, Wearing Masks dan Keeping Distance) During the Covid-19 Pandemic in Durin Simbelang Village Pancur Batu 2020 - Sihite, Yeyen Indriani (Sean Institute, 2022)
Corona virus is a disease that spreads quickly caused by the Corona virus that attacks the human respiratory system with symptoms of fever, cough, sore throat, shortness of breath, fatigue and lethargy. Therefore, efforts to break the chain of transmission are carried out by implementing health protocols including 3M knowledge (washing hands, wearing masks and maintaining distance). The purpose of this study is to determine the description of 3M knowledge in the community in Durin Simbelang Pancur Batu village in 2022. This study uses a descriptive method. Sampling technique using purposive sampling with a sample of 50 respondents. The measuring instrument uses is a questionnaire. The results of this study show that the knowledge of respondents washing hands of the majority was very good 47 people (94%) and minorities were enough 1 person (2%), the knowledge of wearing masks was the majority was very good 45 people (90%) and minorities were good 5 people (10%), and the knowledge of maintaining distance of the majority was very good 34 people (68%) and minorities less 1 person (2%), and the knowledge of 3M the majority was very good 46 people (92%) and the minority was good 4 people (8%). It is expected that the people of Durin Simbelang Pancur Batu can do 3M well in their daily lives.